2019
DOI: 10.1080/10888705.2019.1646134
|View full text |Cite
|
Sign up to set email alerts
|

We Don’t Train in Vain: A Systematic Review and Meta-Analysis of Human and Canine Caregiver Training

Abstract: A meta-analytic review was conducted to assess the current knowledge regarding caregiver training effectiveness for human-human and human-canine dyads. The results showed that most canine-related sources (66%; n=19) were case studies reporting a decrease of learner undesired behavior when using oral instruction/advice (21%; n=6). Most of the human-related research used singlecase designs (57%; n=26) reporting an increase in desired learner behavior (22%; n=10) when caregivers received multi-component training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 111 publications
2
1
0
1
Order By: Relevance
“…In agreement with published behavior-analytic research in the human behavior change arena [ 114 , 115 , 116 , 117 ], MBL across-subjects designs were the most frequently used type of SCRM, which yielded a medium summary effect size (Tau-U 0.90, CI 95% = [0.65, 1]). A moderator analysis for MBL across-subjects designs (meta-regression; Table 10 ) found that this type of MBL design had an impact on the effectiveness of the interventions across all species.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In agreement with published behavior-analytic research in the human behavior change arena [ 114 , 115 , 116 , 117 ], MBL across-subjects designs were the most frequently used type of SCRM, which yielded a medium summary effect size (Tau-U 0.90, CI 95% = [0.65, 1]). A moderator analysis for MBL across-subjects designs (meta-regression; Table 10 ) found that this type of MBL design had an impact on the effectiveness of the interventions across all species.…”
Section: Discussionsupporting
confidence: 82%
“…The variable learner species had moderating capabilities for the effectiveness of clicker training, yielding a larger effect for horses than for dogs and goats. Although the finding that learner species can influence the effectiveness of interventions is in line with an earlier meta-analysis investigating the effectiveness of caregiver training programs for both human and non-human animal learners [ 114 ], the current findings should be interpreted carefully. Half of the eligible studies used horses, while two studies used dogs and only one study featured goats.…”
Section: Discussionsupporting
confidence: 62%
“…renforcement des comportements adaptés, conséquences immédiates et naturelles aux comportements adaptés de l'enfant) a permis d'améliorer non seulement les compétences expressives de l'enfant, mais aussi de réduire l'occurrence de comportements externalisés. De plus, les auteurs ont mis en évidence que l'amélioration du comportement constituait un médiateur de l'amélioration du langage sur le long terme Sadovsky et al, 2020),. dont les recoupements symptomatologiques sont aujourd'hui reconnus avec les TDL(Verhoeven et Balkom, 2003).…”
unclassified
“…The education of dog-owners on bringing up dogs is typically focussed on training, but owners may benefit additionally from advice on more general ways of interacting with dogs as expressed in dog-directed parenting styles. Presently, the education of dog owners targets mainly the training of the dog (Pfaller-Sadovsky et al, 2019), including training the dog to be calm when left alone or obey commands to sit, stay or heel (Braem and Mills, 2010;Deldalle and Gaunet, 2014;Kutsumi et al, 2012;Pfaller-Sadovsky et al, 2019). Scientific research has evaluated the outcomes of different training methods, comparing methods based strongly on reinforcement or punishment (Braem and Mills, 2010;Deldalle and Gaunet, 2014).…”
Section: Introductionmentioning
confidence: 99%